Improving Earth-Science Literacy through Geophysics and Disaster-Mitigation Outreach for Students of SMAN 1 Kuripan - Nila Kurniawati; Ira Chrismawati Hattu Riwu; Nurwahdaniah; Syamsuddin; Suhayat Minardi; Alfina Taurida Alaydrus (Future Tecno-Science Publisher, 2026)
Earth-science literacy needs to be introduced at the secondary-school level because students in West Nusa Tenggara live in an environment affected by tectonic activity, earthquake hazards, and water-resource challenges. This community service program aimed to improve students’ understanding of basic geophysics, earthquake disaster mitigation, and the use of geophysical methods for identifying groundwater potential. The outreach activity was conducted on Saturday, 25 October 2025, at SMAN 1 Kuripan, West Lombok Regency, and involved 67 students. The implementation method consisted of school coordination, preparation of learning materials, interactive presentations, discussion of disaster experiences, earthquake-mitigation simulation, and participatory evaluation through observation, question-and-answer sessions, and teacher feedback. The results indicate that students gained a clearer understanding of the relationship between earth processes, subsurface structures, seismic-wave propagation, disaster preparedness, and the application of electrical-resistivity methods to support groundwater exploration in an area affected by seasonal drought. Student enthusiasm was evident from active discussion, questions related to the 2018 Lombok earthquake, and interest in geoscience study pathways. This activity demonstrates that locally contextualized geophysics outreach can serve as an effective educational strategy for strengthening earth-science literacy, improving disaster-awareness culture, and introducing the role of physics in solving environmental problems.